Mechanistic insights into the interaction between optineurin with RAB8A - Jing Zhang; Lifeng Pan (Autophagy Reports)
OPTN (optineurin), an amyotrophic lateral sclerosis (ALS)-associated modifier, plays vital roles in autophagy and cellular vesicular transport in mammals. OPTN can associate with RAB8A and the GTPase-activating protein TBC1D17, and facilitate the negative regulation of RAB8A by TBC1D17 (TBC domain family member 17). Recently, we reported the biochemical and structural characterizations of the interactions between OPTN, RAB8A and TBC1D17. We determined the crystal structure of the leucine-zipper domain (LZD) of OPTN with the GTP-bound active RAB8A and uncovered the molecular mechanism underpinning the specific interaction of OPTN with RAB8A. Moreover, we revealed that OPTN LZD and the TBC (Tre-2/Bub2/Cdc16) domain of TBC1D17 competitively bind to active RAB8A, while the central coiled-coil domain of OPTN and the active RAB8A can simultaneously interact with TBC1D17 TBC. In summary, our study provided mechanistic insights into the interaction of OPTN with RAB8A, and revealed the interaction relationship among OPTN, RAB8A and TBC1D17.